MORPHOLOGICAL CHANGES SEEN IN THE CONDYLE ASSOCIATED WITH AGE, DENTITION AND TEMPOROMANDIBULAR DISORDERS. - Vijaya Kumaran, Ghayathri; Devi, Sree (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this research is to evaluate the morphological changes in the condylar and its association with age, dentition, and temporomandibular disorders by using panoramic radiography. Patients may complain of severe pain, discomfort, restriction of mouth opening, clicking sound, and more in the temporomandibular region, and therefore it will be correlated with the temporomandibular disorders. The study consists of 100 individuals who visited Saveetha Dental College, Chennai, India, and were categorized into 4 groups according to age: 3-10, 15-20, 30-50, and 60-80 years, with 25 patients in each group. Patients were subjected to digital panoramic radiographs. A questionnaire consisting of 12 questions was designed to record the symptoms, and a clinical examination was performed to record the signs and symptoms of temporomandibular disorders.